Dynamics of humoral immune response in SARS-CoV-2 infected individuals with different clinical stages - Mendez-Cortina, Yorjagis; Rodriguez-Perea, Ana Lucía; Chvatal-Medina, Mateo; Lopera, Tulio Jose; Alvarez-Mesa, Natalia; Rodas-Marín, Jan Karlo; Moncada, Diana Carolina; Rugeles, Maria Teresa; Velilla, Paula Andrea (Frontiers in Immunology, 2022)
Background: The COVID-19 pandemic remains a global health problem. As in other viral infections, the humoral immune response against SARS-CoV-2 is thought to be crucial for controlling the infection. However, the dynamic of B cells in the clinical spectrum of this disease is still controversial. This study aimed to characterize B cell subsets and neutralizing responses in COVID-19 patients according to disease severity through a one-month follow-up. Methods: A cohort of 71 individuals with SARS-CoV-2 infection confirmed by RT-PCR were recruited and classified into four groups: i) asymptomatic; ii) symptomatic outpatients; iii) hospitalized in ward, and iv) intensive care unit patients (ICU). Samples were taken at days 0 (inclusion to the study), 7 and 30. B cell subsets and neutralizing antibodies were assessed using multiparametric flow cytometry and plaque reduction neutralization, respectively. Results: Older age, male gender and body mass index over 25 were common factors among hospitalized and ICU patients, compared to those with milder clinical presentations. In addition, those requiring hospitalization had more comorbidities. A significant increase in the frequencies of CD19+ cells at day 0 was observed in hospitalized and ICU patients compared to asymptomatic and symptomatic groups. Likewise, the frequency of plasmablasts was significantly increased at the first sample in the ICU group compared to the asymptomatic group, but then waned over time. The frequency of naïve B cells decreased at days 7 and 30 compared to day 0 in hospitalized and ICU patients. The neutralizing antibody titers were higher as the severity of COVID-19 increased; in asymptomatic individuals, it was strongly correlated with the percentage of IgM+ switched memory B cells, and a moderate correlation was found with plasmablasts. Conclusion: The humoral immune response is variable among SARS-CoV-2 infected people depending on the severity and time of clinical evolution. In severe COVID-19 patients, a higher plasmablast frequency and neutralizing antibody response were observed, suggesting that, despite having a robust humoral immunity, this response could be late, having a low impact on disease outcome.